Crafting an Inclusive Procurement Policy: Strategies for Embracing Supplier Diversity - Gujar, Harshila (International Journal of Supply Chain and Logistics, 2024)
Purpose: In today's global marketplace, diversity and inclusion have transitioned from mere buzzwords to indispensable elements of successful business practices. A robust procurement policy that embraces supplier diversity not only cultivates a more inclusive supply chain but also drives economic growth and social progress. Methodology: This article examines key strategies for integrating supplier diversity into procurement policies, drawing insights from existing literature and best practices in the field of supply chain management and diversity initiatives. Findings: The article outlines strategies such as incorporating diverse suppliers into Requests for Proposals (RFPs), setting thresholds for diverse supplier consideration, addressing risk acceptance and deviations, and emphasizing genuine efforts over token gestures. It highlights the importance of striking a balance between excellence and diversity while prioritizing active engagement with diverse suppliers. Unique Contribution to Theory, Practice, and Policy: By synthesizing insights from academic research and real-world case studies, this article offers actionable recommendations for organizations seeking to enhance their supplier diversity initiatives. It underscores the necessity of genuine efforts in supplier diversity initiatives, advocating for the integration of diversity considerations into procurement policies to foster economic empowerment, social equity, and long-term sustainability in supply chain operations.